Depression in fathers in the postnatal period: assessment of the Edinburgh Postnatal Depression Scale as a screening measure. - Edmondson, O; Psychogiou, L; Vlachos, H; Netsi, E; Ramchandani, P (2010)
BACKGROUND: Postnatal depression commonly affects women after the birth of a child, and is associated with an increased risk of adverse outcomes for their children. A wide variety of measures have been used to screen for depression in the postnatal period but little research has investigated such measures with men. However depression can also affect men at this time, and this is associated with an independently increased risk of adverse child outcomes. The present study aimed to determine whether a reliable cut off point for the Edinburgh Postnatal Depression Scale (EPDS) can be established to screen fathers. METHOD: A sample of fathers was sent the EPDS at 7 weeks after the birth of their child. A structured clinical interview was conducted with 192 men to determine whether they were suffering from depression. RESULTS: Fathers with depression scored significantly higher on the EPDS than non-depressed fathers. A score of greater than 10 was found to be the optimal cut off point for screening for depression, with a sensitivity of 89.5% and a specificity of 78.2%. LIMITATIONS: The relatively modest participation rate means the results may not be fully generalisable to the whole population. CONCLUSION: The EPDS is shown to have reasonable sensitivity and specificity at a cut off score of over 10. The study shows that it is possible to screen fathers for depression in the postnatal period and it may be valuable to administer this measure to new fathers.